Silicon electrowinning by molten salts electrolysis - Padamata, Sai Krishna; Saevarsdottir, Gudrun (Frontiers in Chemistry, 2023)
Electrochemically produced Si in molten salts can be used to fabricate electronic and photovoltaic devices. The major factors influencing the structure and morphology of Si deposits are electrolyte composition, applied current densities and overpotentials, type of precursors, operating temperature and electrodeposition duration. For Si electrodeposition, a less corrosive electrolyte with the ability to dissolve Si species and easily soluble in water should be used. This review provides a brief analysis of the Si production by electrolysis in molten salts